Ефект кавітації на процес руйнування мікрофлори води - Коваль, І.З.; Шевчук, Л.І.; Старчевський, В.Л. (Видавництво Національного університету «Львівська політехніка», 2009)
The influence of ultrasound on the water disinfection from microorganisms in oxygen atmosphere was considered. Нigh efficiency of the ultrasonic treatment on the investigating process has been determined.
Keywords: мікроорганізми; водойми; бактерії; кавітація; ultrasound; cavitation; microorganisms; disinfection